Die politische Religion. Eine Untersuchung über den Ursprung des Verfalls in der Geschichte (1935) - Schütz, Paul (Hamburg University Press, 2009)
The fourth volume of the "Hamburg Historical research" includes mainly the edition of an so far unpublished text. The author is the theologian Prof. Dr. Dr. Paul Schuetz (1891-1985), who was chief minister from 1940 to 1952 at the Hamburg Main St. Nikolai church and as a full-time lecturer and professor of theology at the University Church of Hamburg. He is among the first who developed a concept of political religion. His 1935 contribution couldn't be published at this time. Today an edition of this contribution is important for theology and church history. Also there is the discussion in historical research of interpreting the "Third Reich" as a "political religion". This model understands dictatorships, especially the National Socialism, as a "political religion", is generally attributed to Eric Voegelin and Raymond Aron, who published their approaches in 1938 and 1939. The fact that Paul Schuetz had three or four years previously developed such a conception, was until recently unknown. The present edition can therefore give new impetus to the debate about the history and viability of this approach and enrich their content.